Masjid architecture : the meaning of masjid - Mohd Nawawi, Norwina (2014)
An introductory lecture to introduce Masjid Architecture from its meaning according to the Al Quran and Sunnah as well as other intepretations for the built environment. The lecture dwell into the actions of prayer, the hierachy of prayer space and location,its message, the physical architectural entity in shape and form and decoration as the framework. Case study on Masjid Nabawi was demonstrated in its evolution. The summary give the audience an insight on the significance of masjid as a place to prostrate when the prayer is called anywhere on earth.